Association between inhaler technique and confidence among hospitalized children with asthma - Litt, Henry K. (Respir Med, 2020)
OBJECTIVE: Proper use of respiratory inhalers is crucial to asthma self-management and associated with improved outcomes. Previous studies conducted in outpatient and community settings show parents and children are overconfident in children’s ability to use inhalers properly, which may lead healthcare providers to not teach or review inhaler technique. This study examined whether children and parents’ confidence were associated with proper inhaler technique among children hospitalized with asthma. METHODS: Children between 5 and 10 years old hospitalized with asthma at an urban academic medical center demonstrated inhaler technique using metered dose inhalers and spacers. Technique was scored based on a validated 12-step scale. Confidence was measured using three items assessing 1. Knowledge to use inhaler, 2. Skills to use inhaler, and 3. Ability to independently use inhaler. These items were five-point scales and analyzed as binary variables. Independent t-tests were used to measure associations between confidence and number of steps performed correctly. RESULTS: None of the confidence items, when asked to parents or children (n = 70), were associated with the number of steps performed correctly. Further, while the majority of children and parents (59–70%) were confident based on each item, the mean number of steps correctly completed was 6.4 out of 12. CONCLUSIONS: Children and parents’ confidence in children’s knowledge, skills, and ability to independently use an inhaler were all poor proxies for proper inhaler technique. Inpatient healthcare professionals should objectively evaluate technique and teach proper inhaler use to all children with asthma to optimize outcomes.